If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (x + 1)(x + -1)(5x + 3) = 0 Reorder the terms: (1 + x)(x + -1)(5x + 3) = 0 Reorder the terms: (1 + x)(-1 + x)(5x + 3) = 0 Reorder the terms: (1 + x)(-1 + x)(3 + 5x) = 0 Multiply (1 + x) * (-1 + x) (1(-1 + x) + x(-1 + x))(3 + 5x) = 0 ((-1 * 1 + x * 1) + x(-1 + x))(3 + 5x) = 0 ((-1 + 1x) + x(-1 + x))(3 + 5x) = 0 (-1 + 1x + (-1 * x + x * x))(3 + 5x) = 0 (-1 + 1x + (-1x + x2))(3 + 5x) = 0 Combine like terms: 1x + -1x = 0 (-1 + 0 + x2)(3 + 5x) = 0 (-1 + x2)(3 + 5x) = 0 Multiply (-1 + x2) * (3 + 5x) (-1(3 + 5x) + x2(3 + 5x)) = 0 ((3 * -1 + 5x * -1) + x2(3 + 5x)) = 0 ((-3 + -5x) + x2(3 + 5x)) = 0 (-3 + -5x + (3 * x2 + 5x * x2)) = 0 (-3 + -5x + (3x2 + 5x3)) = 0 (-3 + -5x + 3x2 + 5x3) = 0 Solving -3 + -5x + 3x2 + 5x3 = 0 Solving for variable 'x'. The solution to this equation could not be determined.
| 64x^2-4y^2+256=0 | | -3+6x=57 | | 4y+6y+6y= | | 8xyz= | | -151=4x-4(-3x+6) | | 10-9=20+9x | | y=(x-3)x^2+1 | | 3x+(-14)=22 | | 5x+7y=-13 | | 20x+15=40+9x-2 | | f(-4)=5 | | 4x(13-5)= | | x+2=n+(3-4) | | -4+8=4 | | ln(x)=.04 | | 1.08+b=15.72 | | x^6+2x^4-3x^2=0 | | 3k-10=k-2 | | A=5+0.5d | | 2x-3y=x-3y | | (6x-12)-2(x-4)= | | 4x-4=8+1x | | -45=25n-17 | | 7(3x+3)=35 | | 12-2t=30 | | 6a-4=36 | | 13x-7x=12-36 | | 25+.10x=40+.05x | | 2x^2-4x-3y=0 | | 0=5(2a^2-95a+480) | | 0=x^2+10x-21 | | 9x=4x-20 |